Critical Latitude. (2nd July 2016) - Pavel, Thomas
Abstract : From his educational background both in France and America, Professor Pavel not only expresses his endorsement, understanding and judgment of the concept of "imposed interpretation, " but also his opinion and further academic expectations. The article has three parts. First, he confirms the existence of the specific problems of "imposed interpretation, " "subjective assumption prior to interpretation, " and "reversed route of cognition." Second, he points out that the phenomen on of imposed interpretation is not unique in contemporary times and has existed in Western literary research since the beginning of the 19 th century— from the Zeitgeist of the age of Hegel, the social environment of positivism, the narratology of structuralism, and to contemporary literary critique, all of which have the feature of using concepts to cover the multiformity of literary works. Pavel finally points out that the contemporary phenomen on of "imposed interpretation" embodies the features of American culture and exposes the problem of American education. He hopes that scholars can keep critical latitude and vitality while rectifying the errors in literary research.